(untitled) (Colombia Medica, 2015)
Background: In Colombia, dengue is an endemic disease and the four serotypes have been reported. The objective of present study was to describe the frequency and severity of dengue in an area of the Colombian Caribbean (department of Cordoba) Methodology: A retrospective study was conducted. Two data sources were analysed: The database from the Direction of Health in Córdoba, and clinical registers of patients diagnosed with haemorrhagic fevers and fevers of unknown origin in reference hospitals. Results: The mean incidence of dengue between 2003-2010 was 36.5 cases per 105 inhabitants (CI95%: 34.3 – 37.5) and adjusted for sub-reporting, could be between 178.5 and 521.6. The mean incidence of severe dengue was 4.7 cases per 105 inhabitants (CI95%: 4.3 – 5.0). Mean mortality rate due to dengue was 0.3 cases per 105 inhabitants. The fatality rate was below 1%. The mean total leukocyte count in patients with dengue was 6181 mm3 (CI95%: 5973 – 6389) and with Severe Dengue it was 4729 mm3 (CI95%: 4220 – 5238). The average platelet count in patients with Dengue was 118,793/mm3 (CI95%: 107,255 – 130,331) and in patients with Severe Dengue 77,655 (CI95%: 59,640 - 95,670). Both differences were statistically significant (p< 0.05). The frequency of laboratories test per patient in patients with Dengue and Severe Dengue were different. Conclusion: The department of Cordoba is a highly endemic zone of Dengue and Severe Dengue in the Colombian Caribbean.